Redox-Sensitive Targeted Doxorubicin-Loaded Chitosan-based Nanoparticles to Treat Breast Cancer - Mahsa Babaei; Soheila Kashanian; Zahra Salemi; Hossein Zhaleh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The positive charge of chitosan (Cs) polymer has limited its utilization as a carrier for doxorubicin (DOX). Herein, a Cs derived by covalent linkage to L-Cysteine (L-Cys) was offered to reduce the positive charge of the polymer and to enhance the DOX entrapment efficiency (EE). Hence, the hyaluronic acid-targeted DOX-loaded Cs-Cys nanoparticles (HA/Cs-CysNPs-DOX) were synthesized as a redox-responsive carrier for intracellular delivery of DOX. At first, the Cs-CysNPs-DOX was synthesized by ion-gelation technique, after which HA was attached by electrostatic interaction as a targeting agent. Ultimately, they were characterized in terms of size, zeta potential, EE, drug loading (DL), and morphology. HA/Cs-CysNPs-DOX based on the novel copolymers displayed an appropriate EE for DOX and redox-stimuli drug release. The hemolysis assay proved the safety and hemocompatibility of the NPs, which confirms their intravenous application. In vitro drug release indicated high stability in physiological conditions with a glutathione (GSH) dependence drug release. The cytotoxicity and apoptosis of HA/Cs-CysNPs-DOX were also studied by investigating MCF-7 cells with various concentrations and times. A considerable cytotoxicity enhancement was displayed for HA/Cs-CysNPs-DOX compared to Cs-CysNPs-DOX and free DOX, while no cytotoxicity effects were found for free NPs. The caspase-3 activity showed that apoptosis was enhanced by raising the concentration of DOX, and the free NPs did not exhibit any caspase-3 activity. Overall, the developed HA/Cs-CysNPs-DOX displayed a high potential for targeted therapy and effective applications in biomedical investigation.